Isolasi dan Identifikasi Bakteri Pendegradasi Limbah Cair Minyak Kelapa Sawit (Elaeis guineensis Jacq) - Hasni Aida; Kartika Manalu (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The purpose of this study was to determine the presence of degrading bacteria in the Simangalam river containing palm oil wastewater in Gunung Melayu Village, North Labuhanbatu Regency. This research was conducted using a survey method on the presence of bacteria and the characteristics of bacterial isolates degrading palm oil industrial wastewater and the data obtained were analyzed descriptively. The results showed that only HB1ST1 and HB2ST2 were circular, while HB3ST2, HB4ST2, HB5ST2, and H62ST2 were irregular. After gram staining, three gram-positive bacterial isolates (HB1ST1, HB4ST2, and HB6ST2) and three gram-negative bacterial isolates (HB2ST2, HB3ST2, and HB5ST2) were obtained. The HB1ST1 isolate motility test showed negative results, while the other five isolates (HB2ST2, HB3ST2, HB4ST2, HB5ST2, and HB6ST2) showed positive results. The conclusion of this study is that there are 6 bacterial isolates that are able to degrade oil palm liquid waste in the Simangalam River from 2 samples of oil palm liquid waste. Keywords: Descriptive, Isolate, Palm Oil Effluent